2007
DOI: 10.1111/j.1365-2249.2007.03545.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of immunoglobulins (IgG, IgA, IgM) in a general adult population and their relationship with alcohol consumption, smoking and common metabolic abnormalities

Abstract: SummaryThe present study investigated serum immunoglobulin (Ig) concentrations in relation to demographic factors, common habits (alcohol consumption and smoking) and metabolic abnormalities in an adult population-based survey including 460 individuals. Serum levels of interleukin (IL)-6, a marker of inflammation, were also determined. After adjusting for confounders, male sex was associated positively with IgA levels and negatively with IgM levels. Age was associated positively with IgA and IgG levels. Smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
450
4
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(516 citation statements)
references
References 42 publications
59
450
4
3
Order By: Relevance
“…31 Besides, the interactions between smoking and genetic effects on the IgG subclasses (IgG1, IgG2 and IG3) have been demonstrated in previous study. 7 Although in our two-stage GWA study, serum IgG level in smokers is significantly lower than that in non-smokers, which is consistent with previous studies; 7,9 there is no significant interaction between smoking and any of the three identified SNPs in determining the serum level of IgG. Nevertheless, the suggestion that the phenotype of TNFRSF13B mutations is affected by geneenvironment factors has been proposed by several studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…31 Besides, the interactions between smoking and genetic effects on the IgG subclasses (IgG1, IgG2 and IG3) have been demonstrated in previous study. 7 Although in our two-stage GWA study, serum IgG level in smokers is significantly lower than that in non-smokers, which is consistent with previous studies; 7,9 there is no significant interaction between smoking and any of the three identified SNPs in determining the serum level of IgG. Nevertheless, the suggestion that the phenotype of TNFRSF13B mutations is affected by geneenvironment factors has been proposed by several studies.…”
Section: Discussionsupporting
confidence: 90%
“…6 Multitudinous environmental factors including infections, smoking and chemical compounds can contribute to this variation. [7][8][9] Reports of pedigree studies or twin studies 10,11 have shown that genetic factors are more important than environmental exposures in determining serum immunoglobulin level in human. 12,13 The values of genetic heritability was h 2 ¼ 0.617 þ 0.020 for IgG.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of food specific IgG has been emphasized as a significant factor in chronic inflammatory diseases, recently. IgG is also claimed to play a role in development of obesity [ 40,41 ]. In a previous study carried out to analyze the correlation between early aterosclerotic lesions in obese and normal-weight children, good antigens, C-reactive protein (CRP) and carotid artery intima media thickness (IMT) were measured and IgG antibodies were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this is not clear. Interestingly, older people tend to have higher serum concentrations of immunoglobulins A and G (Gonzalez-Quintela et al 2008). It is possible that increased immunoglobulins indicate an increased inflammatory state at old age.…”
Section: Ig Kappamentioning
confidence: 99%